Examining the importance of employee engagement in low-contact service models - Morgan, Heather (Kansas State University, 2017)
A significant body of academic work has amassed supporting the importance of employee engagement in the workplace and its ability to influence business outcomes. However, much of this research has been concentrated in high-contact occupations in which the relationship between the employee and the customer is prolonged and involved (e.g., financial consulting, nursing, etc.). The current study utilized movie theatre environments to determine if the ability of employee engagement to influence service delivery and business outcomes persists in low-contact service environments. This research found that even in settings characterized by brief and perfunctory employee-customer interactions, employee engagement at the business unit level significantly influenced service delivery as measured by the resulting overall guest satisfaction. Furthermore, this relationship was fully mediated by guest satisfaction with friendliness of employees, speed of service and cleanliness of the environment which previous research has found to be the primary drivers of overall guest satisfaction within this environment. Partial support was found for the ability of employee engagement to significantly predict reductions in employee turnover as well as reductions in operational inefficiency and negligence. No support was found linking employee engagement to the productivity/profitability of the business unit. Given these research findings which provide additional support for the importance of having an engaged workforce, we examined how employee satisfaction with various aspects of the company and occupational environment correlate to the employee’s level of engagement. We further segment these correlations by demographic groups to better understand the relationships and more effectively target future initiatives geared toward the improvement of employee engagement.
Keywords: Employee engagement; Low contact; Customer satisfaction